2001
DOI: 10.1046/j.1365-3083.2001.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Homing and Ig Secretion in the Murine Mammary Gland

Abstract: In mice the majority of the immunoglobulins (Ig) in milk belongs to the IgA class. Prior to its transepithelial transportation into the milk, dimeric IgA (dIgA) is bound to the transmembrane form of the secretory component or polymeric Ig receptor (SC/pIgR). The latter is synthesized in the epithelial cells lining the ducts and alveoli of the mammary gland. A candidate for playing the role of adhesion molecule to primed lymphocytes present in the murine mammary gland might be the mucosal addressin cell adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…Immediately postpartum, this is achieved by seconding IgA at mucosal surfaces into the serum, which results in a rapid increase in circulating polymeric IgA that permits loading of IgA into the milk via the blood, such that all IgA in milk from 4-day lactating dams is serum derived (26,27). By around day 8 of lactation, substantial numbers of mucosally derived IgA plasma cells have migrated to the mammary glands to establish local production, such that the proportion of serum-derived IgA decreases to below 25% of the total milk IgA (57,60,61). The density of IgA plasma cells in the mammary glands continues to increase up to day 18 of lactation in concert with increased expression of polymeric immunoglobulin receptor and SC (57,60).…”
Section: Discussionmentioning
confidence: 99%
“…Immediately postpartum, this is achieved by seconding IgA at mucosal surfaces into the serum, which results in a rapid increase in circulating polymeric IgA that permits loading of IgA into the milk via the blood, such that all IgA in milk from 4-day lactating dams is serum derived (26,27). By around day 8 of lactation, substantial numbers of mucosally derived IgA plasma cells have migrated to the mammary glands to establish local production, such that the proportion of serum-derived IgA decreases to below 25% of the total milk IgA (57,60,61). The density of IgA plasma cells in the mammary glands continues to increase up to day 18 of lactation in concert with increased expression of polymeric immunoglobulin receptor and SC (57,60).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we could not shed light on the mechanism responsible for the suggested PRL modulation of T-cell homing to MG as no major changes in the mRNA expression of CCR1, CCR2, CCR7, CXCR3, and CXCR5 chemokine receptors were found. To support this notion, reports indicate that at least two adhesion molecules, MadCam and a4 b7, are involved in MG homing during pregnancy and lactation (Tanneau et al 1999, van der Feltz et al 2001, Nishimura 2003, Bourges et al 2008. The possibility cannot be excluded that additional changes may occur during T-cell recruitment and maintenance in MG, involving addressins, integrins, and chemokine receptors' expression on T cells as well as chemokine production by mammary epithelial cells under hormone/cytokine stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known since the 1970s that plasma cells from gut-associated lymphoid tissue are recruited to MG expressing specific adhesion molecules such as CD44 and CD62L and produce mainly IgA to be secreted to milk, transferring immune protection to neonates . Mammary IgA-secreting cell numbers increase during pregnancy in parallel with mammary lobulo-alveolar compartment expansion, reaching maximal levels post partum (Parmely & Manning 1983, Tanneau et al 1999, van der Feltz et al 2001. Lymphocyte homing is an extremely highly regulated mechanism modulated by chemokines, cytokines, integrins, and addressins (Kunkel & Butcher 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The MAd-CAM-1 staining area increases during pregnancy and then decreases during lactation; however there is no change in the number of ß 7 + /c-IgA + cells during pregnancy, and they increase during lactation. Another investigation [49] has also showed that IgA-producing plasma cell numbers and MAdCAM-1 expression are not related. These results invoke the involvement of other factors in the mediation of lymphocyte migration in the lactating mammary gland.…”
Section: Other Potential Lymphocyte Trafficking Mediator Molecules Inmentioning
confidence: 97%
“…Adhesion molecules [14,29] belong to one of these families that mediate lymphocyte trafficking, and chemokines [3,41] are the others. Nishimura et al [34][35][36] and other investigators [42,49] found that some of these molecules are expressed in the mammary gland. This review is focused on these molecules, especially glycosylation-dependent cell adhesion molecule-1 (GlyCAM-1) and mucosal addressin cell adhesion molecule-1 (MAdCAM-1) in the mammary gland.…”
Section: Introductionmentioning
confidence: 93%